Knock on any door - Motley, Willard 1909-1965; Antheil, George 1900-1959 (Powerhouse Films, 2024)
"Milieueinflüsse in den Slums einer amerikanischen Großstadt und sadistische Methoden in der Besserungsanstalt treiben einen jungen Mann bis zum Mord an einem Polizisten. Ein Anwalt verteidigt ihn nicht nur, sondern klagt auch die Gesellschaft an, die den Jugendlichen formte und erst zum Angeklagten machte. Rays Auseinandersetzung mit dem Thema Jugenddelinquenz ist engagiert und sozialkritisch in den Gerichtsszenen, wenngleich oberflächlicher als in der Romanvorlage. Der Film überzeugt eher durch seine darstellerische Qualität, weniger aber durch seine Theorie über das Verbrechen." [filmdienst.de]
Original: USA 1949
Indicator Blu-ray edition special features: High Definition remaster ; original mono audio ; audio commentary with writer and film historian Pamela Hutchinson (2022) ; Nobody knows how anybody feels (2022, 20 mins): appreciation by critic and film programmer Geoff Andrew ; Tuesday in November (1945, 17 mins): documentary short about the democratic process in America, made as part of the Office of War’s The American scene series and boasting Nicholas Ray as assistant director ; theatrical trailer ; image gallery: promotional and publicity material ; new and improved English subtitles for the deaf and hard of hearing
Bildformat 1.37:1
Keywords: Film; Blu-Ray-Disc